2018
DOI: 10.3897/phytokeys.95.21586
|View full text |Cite
|
Sign up to set email alerts
|

Paraboea wenshanensis, a new species of Gesneriaceae from Yunnan, China

Abstract: Paraboea wenshanensis is a new species of Gesneriaceae from Yunnan, China and is described and illustrated here. It is morphologically similar to P. angustifolia, P. martinii and P. glutinosa, but the congeners of this new taxon can be distinguished by several salient characters. A description of P. wenshanensis, together with illustrations and photographs, a distribution map and conservation assessment are presented.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 13 publications
1
2
0
Order By: Relevance
“…With further observation, it is similar to P. glanduliflora Barnett in glandular hairs outside the corollas and different in the basal leaves (Wang et al 2012). After careful comparison with the other species of Paraboea in China (Li 1987;Wang 1990;Fang et al 1995;Li and Wang 2004;Chen et al 2008Chen et al , 2012Chen et al , 2017He et al 2018) and bordering countries (Thúợngtiền 2000;Xu et al 2008), we confirmed that the species represents an undescribed species of Paraboea in Gesneriaceae. After a complete examination to the main worldwide herbaria, we confirmed several additional specimens collected in the adjacent karst regions in China during the 2001-2018 period.…”
Section: Introductionsupporting
confidence: 68%
See 1 more Smart Citation
“…With further observation, it is similar to P. glanduliflora Barnett in glandular hairs outside the corollas and different in the basal leaves (Wang et al 2012). After careful comparison with the other species of Paraboea in China (Li 1987;Wang 1990;Fang et al 1995;Li and Wang 2004;Chen et al 2008Chen et al , 2012Chen et al , 2017He et al 2018) and bordering countries (Thúợngtiền 2000;Xu et al 2008), we confirmed that the species represents an undescribed species of Paraboea in Gesneriaceae. After a complete examination to the main worldwide herbaria, we confirmed several additional specimens collected in the adjacent karst regions in China during the 2001-2018 period.…”
Section: Introductionsupporting
confidence: 68%
“…(Gesneriaceae), including about 90 species, mainly occurs in Bhutan, China, Indonesia, Malaysia, Myanmar, Philippines, Thailand and Vietnam (Xu et al 2008). Recently, several new species have been published (Chen et al 2008(Chen et al , 2012Kiew 2010;Xu et al 2012;Wen et al 2013;He et al 2018). Most of them are distributed in the karst regions in South China and Indo-China (Li 1987;Wang 1990;Xu 1993;Fang et al 1995;Zhu et al 2003;Li and Wang 2004;Shui and Chen 2006;Zhu 2007;Shui et al 2017).…”
Section: Introductionmentioning
confidence: 99%
“…28 species in China, mainly in limestone areas of south and southwest China. Since then, one new species and one new record have been discovered in China (He et al 2018;Lu et al 2019). During our expeditions to Wuyang River, Zhenyuan County and Yuntai Mountain, Shibing County, Guizhou, China in 2016 and 2017, an unidentified species of Paraboea was collected.…”
Section: Introductionmentioning
confidence: 99%